Male-dependent resistance to Spiroplasma-induced cytoplasmic incompatibility - Marie Pollmann; Ronja Reinisch; Lea von Berg; Molly Avidan King; Marina Geiselmann; Lena-Maria Käppeler; Raz Leibson; Natascha Traub; Johannes L. M. Steidle; Yuval Gottlieb (Royal Society Open Science)
Cytoplasmic incompatibility (CI) caused by bacterial endosymbionts is an embryonic developmental failure between infected host males and uninfected females. Although even closely related hosts can have different CI phenotypes, little is known on the resistance mechanism in non-susceptible hosts. The parasitoid wasp species complex of Lariophagus distinguendus encompasses at least three species, termed clades A, B and C. All three species contain strains infected with the endosymbiotic bacterium Spiroplasma, which causes CI in clade A. We studied the relatedness of Spiroplasma in the species complex, the occurrence of CI in selected strains, and the effect of host strain and sex on CI induction. According to multi-locus sequence typing, all host species carry the same sDis strain. CI was absent in strains of clades B and C. Cross-transferring sDis revealed a male-dependent CI resistance in clade B. Together, this suggests a single infection event in the ancestor of all L. distinguendus clades. Some L. distinguendus strains are susceptible to CI, others are resistant. At least in one strain, resistance to CI is male-dependent, as theory predicts, supporting male-dependent traits as drivers for loss of CI-inducing bacteria. These results facilitate future studies on the mechanism of Spiroplasma-induced CI and its resistance.